LGG-49. MOLECULAR ALTERATIONS IN PREGNANT ADOLESCENT AND YOUNG ADULT WOMEN WITH GLIOMA. Issue 2 (22nd June 2018) - Bennett, Julie; Ryall, Scott; Zapotocky, Michal; Stucklin, Ana Guerreiro; Fukuoka, Kohei; Das, Sunit; Mason, Warren; Perry, James; Sahgal, Arjun; Aldape, Kenneth; Keith, Julia; Munoz, David; et al.
Abstract: INTRODUCTION: Brain tumors account for 10% of tumors in adolescents and young adults (AYA), with gliomas being most common. This age overlaps with peak fertility in women. Previous case series suggested a link between progression/transformation of gliomas during pregnancy. Molecular alterations in this group is unknown. We sought to identify a cohort of AYA women, describe tumor behavior during pregnancy and define molecular alterations. METHODS: An institutional review was conducted identifying women 15-39.9 years with glioma and pregnancy at initial diagnosis or during treatment. Tumor specimens were tested for common molecular alterations. RESULTS: Of 217 female patients identified, 8 were diagnosed with glioma during pregnancy (1 pilocytic astrocytoma, 1 diffuse astrocytoma, 4 oligodendrogliomas, 2 anaplastic astrocytomas and 1 glioblastoma multiforme). Of these, 6 tumors underwent molecular testing: 2 with loss of heterozygosity of 1p/19q (oligodendrogliomas), 1 with IDH-1 mutation (DA) and 3 with no alterations found (PA, AA, GBM). Importantly, no tumors harbored common MAPK pathway alterations. Median gestational age was 32 weeks (range 8-38), with one patient undergoing therapeutic abortion prior to treatment for tumor. Three additional patients had malignant transformation during pregnancy (2 DA transformed to GBM, 1 DA transformed to AA), with one IDH-1 mutation identified (DA to GBM) and one with no alteration found. CONCLUSIONS: Molecular alterations in this population corresponded to those typically seen in adult tumors, with no pediatric-type alterations found. Malignant transformation is a possibility and patients should be counselled on this risk. Therapeutic abortion should be considered in extreme situations.